Reconstitution reveals how myosin-VI self-organises to generate a dynamic mechanism of membrane sculpting - Rogez, Benoît (2019)
One enigma in biology is the generation, sensing and maintenance of membrane curvature. Curvature-mediating proteins have been shown to induce specific membrane shapes by direct insertion and nanoscopic scaffolding, while the cytoskeletal motors exert forces indirectly through microtubule and actin networks. It remains unclear, whether the manifold direct motorprotein–lipid interactions themselves constitute another fundamental route to remodel the membrane shape. Here we show, combining super-resolution-fluorescence microscopy and membrane-reshaping nanoparticles, that curvature-dependent lipid interactions of myosin-VI on its own, remarkably remodel the membrane geometry into dynamic spatial patterns on the nano- to micrometer scale. We propose a quantitative theoretical model that explains this dynamic membrane sculpting mechanism. The emerging route of motorprotein–lipid interactions reshaping membrane morphology by a mechanism of feedback and instability opens up hitherto unexplored avenues of membrane remodelling and links cytoskeletal motors to early events in the sequence of membrane sculpting in eukaryotic cell biology. Curvature-mediating proteins are known to induce specific membrane shapes, but whether motorprotein-lipid interactions remodel membranes too remains unclear. Here authors show that curvature-dependent lipid interactions of myosin-VI remodel the membrane geometry into dynamic spatial patterns.